Monetäre Ursachen der Arbeitslosigkeit in Currency Board-Systemen? - Ole Janssen; Armin Rohde (Universität Greifswald, Rechts- und Staatswissenschaftliche Fakultät, 2002)
– The rule bounded currency board-system is a contribution to a process of convergence between the price level of the currency board-country and the anchor currency-country. However this strategy includes the risk of an inadequate provision with liquidity in the currency board-country. In the long run this corresponds to the risk of increasing the structural unemployment. Keeping up the currency board-principle of a sufficient reserve backing, the orientation of the monetary expansion to the inevitable inflation rate may reduce this risk. However it also raises the risk of a reduced credibility concerning monetary policy and price level stability. In conclusion there exists a trade-off between the credib ility of monetary discipline and therefore price level stability, and the monetary flexibility and employment and therefore the credibility of keeping up the currency board-system in the long run.
Keywords: 330; Currency Board; Inflationsbekämpfung; Beschäftigungseffekt; Arbeitslosigkeit; Theorie